A Metabolite-Based Resistance Mechanism Against Malaria - Figueiredo, Ana; Rastogi, Sonia Trikha; Ramos, Susana; Nogueira, Fátima; De Villiers, Katherine; Sousa, António GG; Votborg-Novél, Lasse; von Wedel, Cäcilie; Tober-Lau, Pinkus; Jentho, Elisa; Pagnotta, Sara; Mesquita, Miguel; et al. (American Association for the Advancement of Science, 2026)
INTRODUCTION
Jaundice arises when bilirubin, a yellow pigment, accumulates in plasma and gives a yellowish color to the skin and the sclera (the white portion of the eyeball). Bilirubin has long been considered as a “waste product” of heme catabolism. Because of its lipophilic nature, bilirubin excretion requires conjugation to glucuronic acid through a reaction catalyzed in hepatocytes by UDP glucuronosyltransferase family 1 member A1 (UGT1A1). The less toxic water-soluble conjugated bilirubin is then excreted via the bile into the intestinal lumen. Because bilirubin conjugation occurs in the liver, its accumulation in plasma is a reliable biomarker of liver dysfunction. Although accurate, this has led to the widespread perception of jaundice being a maladaptive and eventually pathogenic response. However, several investigators have shown that bilirubin participates in various activities, acting as a lipophilic antioxidant and presumably as a ligand of receptors involved in different metabolic functions.
RATIONALE
Jaundice is a common presentation of malaria, the ancestral infectious disease caused by parasites from the Plasmodium genus. These parasites evolved to invade and proliferate inside the red blood cells of their hosts, causing hemolysis and the accumulation of extracellular hemoglobin in plasma. When the prosthetic heme groups of hemoglobin are detached from the globin chains of hemoglobin, there is an accumulation of labile heme in plasma, an independent risk factor for Plasmodium falciparum malaria severity. Survival from experimental malaria is contingent on the capacity of the infected host to catabolize heme into biliverdin, the substrate used by biliverdin reductase to produce bilirubin. This raised the hypothesis that bilirubin production by biliverdin reductase participates in a metabolism-based defense strategy against malaria.
RESULTS
Using a highly specific approach to measure bilirubin in plasma, we found a correlation between the levels of circulating unconjugated bilirubin and the onset of symptomatic P. falciparum malaria in humans. We established that bilirubin is protective against malaria in an experimental model of malaria in mice, where repressing bilirubin production through genetic loss of function of biliverdin reductase precipitated malaria mortality. This lethal phenotype could be reversed by the administration of bilirubin, verifying that unconjugated bilirubin can be protective against experimental malaria. Repression of bilirubin conjugation by hepatic UGT1A1 was also protective against experimental malaria in mice, further supporting the protective effect of unconjugated bilirubin against malaria. Using several orthogonal approaches in vivo and in vitro, we found that unconjugated bilirubin targets Plasmodium inside the red blood cell to repress its proliferation and virulence. Bilirubin targets the parasite’s mitochondrion and simultaneously interferes with heme detoxification, disrupting the parasite food vacuole and therefore inhibiting the acquisition of essential amino acids from hemoglobin.
CONCLUSION
The induction of bilirubin production and inhibition of its conjugation in response to Plasmodium spp. infection is an evolutionarily conserved resistance mechanism against malaria. Presumably, this metabolism-based defense strategy has a major evolutionary trade-off, namely, the insidious incidence of neonatal jaundice, which can potentially damage neurons in the brain. To what extent this defense strategy can be targeted therapeutically to overcome the enormous burden imposed by malaria on human populations remains to be established.